Evaluation of human capital as a factor of economic growth with the help of example from IT industry - Prudnikov, Pavel; Brůna, Karel, 1973-; Dvořák, Michal; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The purpose of the graduation thesis is to study the assessment of the impact of human capital on economic growth based on IT -- sector example. In the final thesis was defined essence of human capital, its role as a production factor, was examined method of human capital evaluation, presented the results of assess of the human capital impact on the company's capitalization and the company's economic growth. The main factor of using VHC formula to calculate the human capital is the availability of the data that is why it is possible for calculating human capital with the help of secondary data.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses